Contemplative education as a response to the contradictions between neoliberalism and social justice in the Curriculum Assessment Policy Statement (CAPS) - Bekker, Petrus (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEd)--Stellenbosch University, 2020.